The Accuracy of Nursing Term Translation from Indonesian to English by Nursing Students - Maryani; Ika Puspita Rini (Journal of English Language Teaching and English Linguistics, 2023)
Translating the accuracy of source language into target language in specialized language requires high appropriation that retains of the original meaning. This study aims to discover the accuracy of nursing term translation from Indonesian to English by nursing students. This research is a mixed-method research with content analysis method to analyze the accuracy of translation. The accuracy of the translation results will be analyzed quantitatively and qualitatively. The research subject was the translation of Indonesian – English abstracts of nursing articles by nursing students of STIKES Surya Global Yogyakarta. The object of research was nursing special terms in the form of words and phrases. The data collection technique used was the documentation method used to find related data that has been determined. The results of this study showed that the accurate translation of nursing terms was 65.29% while the inaccurate translation was 34.71%. In addition, there were about 25% of accurate translations was plagiarism. It is considered plagiarism because the student's translation of the abstract was exactly as same as the original writer's English version of the abstract, not only the specific language but also the whole sentence. It can be concluded from this study that overall the translation of nursing students into the special language of nursing is accurate. There are only a few translations is still in low inaccuracy level. Keywords: Accuracy, Nursing term, Translation